Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 8.2

Ex 8.2, 1

Ex 8.2, 2

Ex 8.2, 3 Important

Ex 8.2, 4

Ex 8.2, 5 (a)

Ex 8.2, 5 (b) Important

Ex 8.2, 5 (c)

Ex 8.2, 6

Ex 8.2, 7 Important

Ex 8.2, 8

Ex 8.2, 9 Important

Ex 8.2, 10

Ex 8.2, 11 Important

Ex 8.2, 12

Ex 8.2, 13

Ex 8.2, 14 Important

Ex 8.2, 15

Ex 8.2, 16 Important

Ex 8.2, 17 Important

Ex 8.2, 18 Important

Ex 8.2, 19

Ex 8.2, 20

Ex 8.2, 21

Ex 8.2, 22 Important

Ex 8.2, 23 Important

Ex 8.2, 24

Ex 8.2, 25

Ex 8.2, 26 Important

Ex 8.2, 27 Important

Ex 8.2, 28 You are here

Ex 8.2, 29 Important

Ex 8.2, 30 Important

Ex 8.2, 31

Ex 8.2, 32 Important

Chapter 8 Class 11 Sequences and Series

Serial order wise

Last updated at May 29, 2023 by Teachoo

Ex9.3, 28 The sum of two numbers is 6 times their geometric mean, show that numbers are in the ratio (3 + 2 2) :"(3 2 " 2) Introduction Componendo dividendo If / = / Applying componendo dividendo ( + )/( ) = ( + )/( ) Eg: Taking 1/2 = 4/8 (1+ 2)/(1 2) = (4 + 8)/(4 8) 3/( 1) = 12/( 4) -3 = -3 Ex 8.2, 28 The sum of two numbers is 6 times their geometric mean, show that numbers are in the ratio (3 + 2 2) :"(3 2 " 2) Let a & b be the numbers We know that Geometric mean of two numbers a & b is i.e. GM of a & b = According to the question Sum of two numbers a and b is 6 times of their GM a + b = 6 Solving, ( + )/(2 ) = 3/1 Applying componendo & dividendo ( + +2 )/( + 2 ) = (3 + 1)/(3 1 ) (( )2+( )2+2( ))/(( )2+( )2 2( ) ) = 4/2 Using (x + y)2 = x2 + y2 + 2xy (x - y)2 = x2 + y2 - 2xy ( + )2/( )2 = 2/1 (( + )/( ))^2 = 2/1 ( + )/( ) = 2/( 1) Again applying componendo & dividendo (( + )+( ))/(( + ) ( ) ) = ( 2 + 1)/( 2 1) ( + + )/( + + ) = ( 2 + 1)/( 2 1) (2 + 0)/( + + ) = ( 2 + 1)/( 2 1) (2 )/(2 + 0) = ( 2 + 1)/( 2 1) (2 )/(2 ) = ( 2 + 1)/( 2 1) ( / ) = ( 2 + 1)/( 2 1) Squaring both sides ( ( / ))^2 = (( 2 + 1)/( 2 1))^2 / = (( 2 + 1)2)/(( 2 1)2) / = (( 2)2 + (1)2 + 2 2 1)/(( 2)2 + (1)2 2 2 1) / = (2 + 1 + 2 2)/(2 + 1 2 2) / = (3 + 2 2)/(3 2 2) Thus the ratio of a & b is 3 + 2 3: 3 2 2 Hence proved